Engendering Constructivist Learning in Tertiary Teaching - Giridharan, Beena (David Publishing Company, 2012)
In constructivist teaching, it is expected that students are able to apply skills and knowledge acquired from their course of study to the various situations that they encounter over the course of their professional lives. Constructivist classrooms engage learners actively in the learning process. Learners actively take knowledge, connect it to previously assimilated knowledge and make it theirs by constructing their own interpretation (Cheek, 1992). Formulating one’s teaching philosophy requires reflecting on personal beliefs and pedagogies about teaching and learning, and reviewing and evaluating teaching approaches and visions for teaching. It necessitates aligning personal values with students’ learning needs and setting out clear objectives for teaching. In the constructivist model, students are urged to be actively involved in their own process of learning, on the assumption that individuals construct knowledge instead of receiving it from others. The way in which knowledge is conceived and acquired, the types of knowledge, skills, and activities emphasized, the role of the learner and the teacher, how goals are established: all of these factors are expressed differently from the constructivist perspective (Christie & Stone, 1999). This paper proposes a framework for applying constructivist practices in a social peer learning environment while analyzing its strengths and limitations.